Managing head injury in non-elite field hockey and Australian football: a qualitative study - McManus, Alexandra; Gray, N.; Gauci, R. (Sports Medicine Australia, 2005)
This study aimed to assess the current understanding of traumatic brain injury (TBI) and mild traumatic brain injury (mTBI) in sport, and to identify existing management and return-to-play guidelines associated with these injuries, in non-elite field hockey and Australian rules football. Qualitative research methods were used to assess the current understanding of brain injury, and the usual management procedures and return-to-play guidelines associated with mTBI in two sports. The results indicate that no team had a standardised procedure for the management of head or brain injury in their sport. Findings from the study indicate that the management of head injury was variable, and assessments were made based on the level of expertise of the person managing each injury. The assessments were subjective in nature, and there were no evidence-based guidelines available for the management of mTBI to any of the respondents in this study.